Origin of circulating free DNA in patients with lung cancer - Abe, Tomonori (PLoS One, 2020)
Liquid biopsy has become widely applied in clinical medicine along with the progress in innovative technologies, such as next generation sequencing, but the origin of circulating tumor DNA (ctDNA) has not yet been precisely established. We reported bimodal peaks of long fragment circulating free DNA (cfDNA) of 5 kb and short fragment cfDNA of 170 bp in patients with advanced lung cancer, and both contained ctDNA. In this paper, we demonstrate that the total amount of cfDNA is higher when patients with lung cancer have extrathoracic metastases, and the amount of long fragment cfDNA is significantly higher in those patients. To investigate the origin of long fragment cfDNA, conditioned media isolated from lung cancer cell lines was fractionated. Long fragment cfDNA was found concomitant with extracellular vesicles (EVs), but short fragment cfDNA was not observed in any fractions. However, in peripheral blood from a metastatic animal model both fragments were detected even with those same lung cancer cell lines. In human plasma samples, long fragment cfDNA was observed in the same fraction as that from conditioned media, and short fragment cfDNA existed in the supernatant after centrifugation at 100,000g. Concentration of ctDNA in the supernatant was two times higher than that in plasma isolated by the conventional procedure. Long fragment cfDNA associated with tumor progression might therefore be released into peripheral blood, and it is possible that the long fragment cfDNA escapes degradation by co-existing with EVs. Examination of the biological characteristics of long fragment cfDNA is a logical subject of further investigation.